A long-term field experiment confirms the necessity of improving biowaste sorting to decrease coarse microplastic inputs in compost amended soils. (15th December 2022) - Colombini, Gabin; Rumpel, Cornelia; Houot, Sabine; Biron, Philippe; Dignac, Marie-France
Abstract: Microplastic (MP) input into agroecosystems is of particular concern as their sources are diverse (mulching films, biosolid application, wastewater irrigation, flooding, atmospheric input, road runoff). Compost application, which is needed to sustain soil ecosystem services in the context of a circular economy, may be a source of microplastics. The aim of this study was to evaluate how different composts derived from urban wastes impact the nature and quantity of coarse (2–5 mm) microplastics (CMP) in soils, using a long-term field experiment in France. Composts resulting from different levels of urban waste sorting were investigated. Our approach included the isolation of microplastics from composts and amended soils followed by their characterization using pyrolysis GC/MS spectrometry. We found that coarse microplastic concentrations varied from 26.9 to 417 kg per hectare depending on the compost type, after 22 years of bi-annual application. These values may be higher than for conventional agricultural practices, as application rate was twice as high as for normal practices. Composts made from municipal solid waste were by far the organic amendments leading to the highest quantity of plastic particles in soils, emphasizing the urgent need for limiting plastic use in packaging and for improving household biowaste sorting. Our results strongly suggest that standards regulating organic matter amendment application should take microplastics into account in order to prevent contamination of (agricultural) soils. Moreover, although no impacts on the soil bio-physico-chemical parameters has been noted so far. However, given the huge microplastic inputs, there is an urgent need to better evaluate their effect on soil functioning. Graphical abstract: Image 1 Highlights: Coarse microplastics (CMP) pollution in amended soils depend on compost type. Non-selective waste sorting led to high CMP amount in compost amended soil. Polyethylene and polystyrene were the most abundant CMP in composts and soils. Repeated application of compost can lead toCMP accumulation in soils.